Aplikasi Pendaftaran dan Pemilihan Pengurus OSIS SMK Sudirman 1 Wonogiri Berbasis Website - Yuniarti, Risky, Umi Fadlillah, ST. MEng (2015)
OSIS ( organization school students inter ) is a unit of or group of cooperation among the students who play an important role for schools in achieving a common purpose. OSIS is an organization students who are inside and in the school environment. One SMK ( Vocational High School ) in Sudirman is SMK 1 Wonogiri requiring registration applications and electoral committee OSIS this, for assisting the organisers in regard to prepare elections. Enrollment application of the registration and the selection of office-holders OSIS made by using a programming language they framework open source by the use of the concept of mvc ( of models view of a controller ) supported by codeigniter to adjust library to be called on to in application , and use mysql database. In its testing phase , to give to the assessment in Vocational Sudirman 1 Wonogiri with respondents from the committee , students and a candidate with demonstrating this application directly and give an assessment of respondents through kuisioner already made. Registration application and selection of the expected OSIS that can help the OSIS in managing student data and candidates , to facilitate students in the selection of candidates , and can help candidates in registration and examination through a system that has been made.